Over Education as a Problem of Higher Education Curriculum - Akpunar, Burhan; Ozeren, Ender; Erdamar, F. Selim (Common Ground Research Networks, 2020)
In recent years, the rate of access to higher education has increased dramatically in Turkey. Although this case provides many advantages in the medium and long term, it is also a source of a significant problem. This problem is ”over education“ problem. This study addresses the over education problem in the dimension of education and particularly in the context of higher education curricula. As a result of the documentary analysis, we argue that Turkey can alleviate over education problem by adopting a market-oriented higher education model. © 2020 International Journal of Learning and Teaching. All Rights Reserved.
Keywords: employment; higher education curricula; over education; unemployment